Knowledge and behaviors in relation to antibiotic use among rural residents in Anhui, China. Issue 6 (26th March 2018) - Cheng, Jing; Coope, Caroline; Chai, Jing; Oliver, Isabel; Kessel, Anthony; Wang, Debin; Sun, Yehuan
Abstract: Objectives: To examine antibiotic‐related knowledge and behaviors in rural Anhui, identify factors associated with knowledge, and explore the relationship between knowledge and antibiotic use. Methods: Cross‐sectional study of a random sample of 2760 residents of rural China using structured interviews. Results: The response rate was 94.6%. A total of 2390 respondents (91.6%) believed that antibiotics can control viruses; 2007 (77.5%) respondents thought that a combination of antibiotics is more effective than a single class; and 590 (22.6%) were able to name at least one disbenefit of using antibiotics. Multivariate analysis revealed those with a higher educational level and younger age group had greater knowledge of antibiotics (OR 2.54 and 0.77, respectively). Self‐medication was common with 1052 (out of 2274 responses, 46.3%) of participants use over the counter or leftover medicines for common infections. Greater knowledge was associated with buying drugs without prescription (aOR 2.02; 95% CI, 1.29–3.17) and using leftover medication (aOR 2.80; 95% CI, 1.55–5.06). Conclusion: Knowledge about antibiotics was low and reported use high. Worryingly those with greater knowledge had less desirable behaviors that highlights the urgent need for multifaceted interventions to change behavior.